Analyzing the Adoption of Taxpayer Surveillance Innovations with the Diffusion of Innovations Model and UTAUT - Wangsa, I Wayan Murlanda; Ariyanto, Dodik; Mimba, Ni Putu Sri Harta; Hasibuan, Henny Triyana (Diponegoro University, 2025)
Taxpayer supervision at the Directorate General of Taxes (DGT) faces new regulations requiring comprehensive oversight. The existing core tax system is deemed inadequate, prompting account representative (AR) officers to seek alternatives. The innovation in the form of an end user computing (EUC) applications used in supervision procedure has proven beneficial despite the lack of official support. This study aims to investigate the innovation characteristics that influence innovation adoption within the AR of DGT, drawn from the diffusion of innovation theory (DOI) and combining it with moderating variables of the unified theory of acceptance and use of technology (UTAUT). The study involved 224 AR officers at the DGT Bali regional office, selected through convenience sampling. Hypothesis testing was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate that the characteristics of observability, relative advantage, and compatibility significantly influence AR’s intention to adopt innovation, while complexity and trialability proved insignificant. Furthermore, age, gender, and experience did not significantly moderate the influence of innovation characteristics. In conclusion, this integrated model successfully examined the innovation characteristic factors that influence the adoption of EUC in supervision at DGT. The study has theoretical implications by providing empirical evidence from TDI characteristics combined with the UTAUT model. This study has limitations in collecting AR research sample data only in the Bali Regional Tax Office work unit and data collection at one point in time that is not continuous, so the data is only cross-sectional.